METHODOLOGY FOR DETERMINING THE NEED FOR ECONOMIC RESOURCES OF THE ROAD TRANSPORT COMPLEX - Ravshanov, Malik (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article is devoted to the development of a methodology for determining the need for economic resources of the road transport complex. A mathematical model is proposed for forecasting the demand for various types of resources, based on the demand for industry products.